2020
DOI: 10.1007/978-3-030-60327-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Rate Equations for Graphs

Abstract: In this paper, we combine ideas from two different scientific traditions: 1) graph transformation systems (GTSs) stemming from the theory of formal languages and concurrency, and 2) mean field approximations (MFAs), a collection of approximation techniques ubiquitous in the study of complex dynamics. Using existing tools from algebraic graph rewriting, as well as new ones, we build a framework which generates rate equations for stochastic GTSs and from which one can derive MFAs of any order (no longer limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We used an extension of the κ-calculus (29), in κ language for this study, which is a rule-based stochastic process calculus that is best understood as a graph rewriting system (30,31) for labelled site graphs. It has been extensively used in its original form in molecular biology to study the dynamics of interacting large molecules or polymers, and has been shown to be applicable to population biology and epidemics (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an extension of the κ-calculus (29), in κ language for this study, which is a rule-based stochastic process calculus that is best understood as a graph rewriting system (30,31) for labelled site graphs. It has been extensively used in its original form in molecular biology to study the dynamics of interacting large molecules or polymers, and has been shown to be applicable to population biology and epidemics (45).…”
Section: Discussionmentioning
confidence: 99%
“…We constructed a transmission model using an extended version of the kappa-calculus (29) to implement a transmission model as a stochastic graph rewriting system (30,31), a generalalisation of how explicit epidemic dynamics are usually formulated on networks (32). In this model, individuals have disease progression states and transmission is mediated by place, with a separate transmission process for each setting or kind of place.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, albeit a rewriting-based graphical formalism, Kappa as originally introduced in [23] is not a categorical rewriting formalism, although categorical approaches have been employed to model certain aspects of its semantics [27]. This renders comparing this approach with the computation of commutators presented in this paper highly intricate.On the other hand, an interesting line of work by Danos et al [28,29] demonstrated that at least in the less technically involved setting of rewriting over adhesive categories without conditions or constraints, some of the syntactic methods utilized in the Kappa framework could be reinterpreted in the adhesive rewriting setting in order to obtain algorithms for computing first-order moment ODEs for pattern counting observables 8 , providing a first hint at the possible existence of a general rewriting-based CTMC formalism for Kappa.…”
Section: Ambient Pattern and State Categoriesmentioning
confidence: 99%